como posso resolver essa equação 6 (x - 3) - 9 (x -1) = 5 (x =3), 2 x - 3 = 7 -2 ( 2 x - 13) e 15 + 3 ( x +2 = - 7 x +
rosejuliao:
15 + 3 ( x + 2 ) = - 7 x + 2 ( x + 1 ) são três equações
Soluções para a tarefa
Respondido por
1
a)
6.(x - 3) - 9.(x -1) = 5 - (x +3)
6x - 18 - 9x + 9 = 5 - x - 3
- 3x - 9 = - x + 2
- 9 - 2 = - x + 3x
- 11 = 2x
2x = -11
x = - 11
2
______________________________________________
b)
2x - 3 = 7 - 2.( 2x - 13)
2x - 3 = 7 - 4x + 26
2x - 3 = 7 + 26 - 4x
2x - 3 = 33 - 4x
2x + 4x = 33 + 3
6x = 36
x = 36/6
x = 6
**************************************************
c)
15 + 3.(x + 2 ) = - 7x + 2.(x + 1 )
15 + 3x + 6 = - 7x + 2x + 2
21 + 3x = - 5x + 2
3x + 5x = 2 - 21
8x = - 19
x = - 19
8
******************
6.(x - 3) - 9.(x -1) = 5 - (x +3)
6x - 18 - 9x + 9 = 5 - x - 3
- 3x - 9 = - x + 2
- 9 - 2 = - x + 3x
- 11 = 2x
2x = -11
x = - 11
2
______________________________________________
b)
2x - 3 = 7 - 2.( 2x - 13)
2x - 3 = 7 - 4x + 26
2x - 3 = 7 + 26 - 4x
2x - 3 = 33 - 4x
2x + 4x = 33 + 3
6x = 36
x = 36/6
x = 6
**************************************************
c)
15 + 3.(x + 2 ) = - 7x + 2.(x + 1 )
15 + 3x + 6 = - 7x + 2x + 2
21 + 3x = - 5x + 2
3x + 5x = 2 - 21
8x = - 19
x = - 19
8
******************
Perguntas interessantes